2018
DOI: 10.3329/ajmbr.v3i4.35341
|View full text |Cite
|
Sign up to set email alerts
|

Study on growth traits at weaning and yearling stages of indigenous and F1 crossbred buffalo in Bangladesh

Abstract: This study was planned to clarify the variation of body weight and average daily gain traits in both indigenous and F1 crossbreed (Local×Mediterranean) buffalo at weaning (sixth month) and yearling stages (twelfth month). Data were collected from 33 indigenous and 35 F1 crossbred buffalo progeny during the period of 2011 to 2014 with intensive management system at Research and Development farm of Lal Teer Livestock Limited in Bangladesh. The gathered data were analyzed using general linear model (GLM) and inde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 3 publications
0
0
2
Order By: Relevance
“…These differences may be due to the management and feeding conditions of buffaloes in university farms in Afyon and under breeder conditions in Istanbul. Moreover, while the values are higher than the 73.42 ± 1.65 kg reported for Surti buffaloes by Pandya et al (2015), they are lower than those reported for Mediterranean crossbred buffaloes in Bangladesh (144.14 ± 4.10 kg) by Shahjahan et al (2017). This may be due to differences in breed, geographical and breeding conditions.…”
Section: Resultscontrasting
confidence: 57%
“…These differences may be due to the management and feeding conditions of buffaloes in university farms in Afyon and under breeder conditions in Istanbul. Moreover, while the values are higher than the 73.42 ± 1.65 kg reported for Surti buffaloes by Pandya et al (2015), they are lower than those reported for Mediterranean crossbred buffaloes in Bangladesh (144.14 ± 4.10 kg) by Shahjahan et al (2017). This may be due to differences in breed, geographical and breeding conditions.…”
Section: Resultscontrasting
confidence: 57%
“…Similar findings were obtained in different studies (Thiruvenkadan et al, 2009;Kul et al, 2017;Erdogan et al, 2021;Kaplan, 2021;Alkoyak and Öz, 2022). BW values (175.41 ± 2.06 kg) were found to be higher than the results of earlier research (Thiruvenkadan et al, 2009;Akhtar et al, 2012;Şekerden, 2014;Pandya et al, 2015;Kul et al, 2017;Yılmaz et al, 2017;Erdogan et al, 2021;Kaplan, 2021) for Murrah, Nili-Ravi, Surti, and Anatolian breeds, whereas higher values were reported by some studies (Shahin et al, 2010;Mendes Malhado et al, 2012;Vergara et al, 2012;Falleiro et al, 2013;Agudelo-Gómez et al, 2015;Shahjahan et al, 2017;El-den et al, 2020;Medrado et al, 2021). The least-square means for body measurements were similar to the results of literature (Uslu, 1965;Gürcan et al, 2011;Gavit et al, 2013;.…”
Section: Resultscontrasting
confidence: 56%